Business Actors’ Responsibility for Consumer Losses Due to Product Content Mismatch Skincare Products and Packaging Labels - Ghufriani, Deliana Rinasari; Winanti, Atik (Al-Risalah, 2026)
The rapid growth of the skincare industry in Indonesia has not always been accompanied by adequate compliance with consumer protection laws. One prominent issue is the case of White Tomato products marketed by Dr. Richard Lee, where discrepancies were found between the information on the label and the actual composition of the product, including allegations of relabeling practices that could potentially cause harm to consumers. This study aims to analyze the legal responsibility of business actors for losses arising from such actions and to examine the legal remedies available to consumers. Using a normative juridical method, this study applies a legislative approach and a case approach through a review of relevant regulations and administrative actions issued by the Indonesian Food and Drug Administration (BPOM). The results of the study show that these practices violate the provisions of Law Number 8 of 1999 concerning Consumer Protection, specifically Articles 4, 7, and 8, because they do not provide accurate and clear product information to consumers. Business operators may be held civilly liable under Article 19 of the Consumer Protection Law and Article 1365 of the Civil Code, and may be subject to administrative and criminal sanctions under Articles 61 and 62 of the Consumer Protection Law. Consumers can pursue legal remedies through civil litigation, administrative complaints to the BPOM, or alternative dispute resolution through the BPSK. This study highlights the importance of strict compliance with honest product information and emphasizes the need for stricter regulatory oversight to ensure consumer protection and legal certainty.